Effect of Ketamine on Tourniquet Induced Hypertension - Hayat, Muhammad Umer; Saeed, Mobasher Ahmed; Saeed, Ahmed; Khan, Basit Mehmood; Abbas, Sana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the frequency of tourniquet induced hypertension in patients undergoing limb surgeries under general anesthesia with intravenous infusion of ketamine and placebo (saline infusion).Study Design: Comparative prospective study.Place and Duration of Study: Anaesthesia Department, Combined Military Hospital, Rawalpindi Pakistan, from May to Nov 2018.Methodology: Total 80 patients undergoing upper and lower limb surgeries with tourniquet application under general anesthesia were randomly assigned into two equivalent groups. Group A (n=40) received intravenous ketamine 0.1 mg/kg bolus followed by infusion at a rate of 2ug/kg/min while Group B (n=40) received intravenous bolus of normal saline followed by its infusion via infusion pump. Systolic blood pressures were recorded by non-invasive method 30 seconds prior to tourniquet inflation and at 60 mins interval after its inflation. Results were characterized using the descriptive statistics. Mean and standard deviation (SD) were used for quantitative variables while frequency and percentages for qualitative variables. The p-value